The practice of performance: Studies in musical interpretation - Rink, John (Cambridge Cambridge University Press, 1995)
The twelve essays in this volume reflect the most important trends in the study of musical performance. Three areas are investigated: the psychology of performance, the semantics of performance, and the relation between performance and analysis. The first section broaches fundamental issues such as text, expression, musical motion and the role of practice in the acquisition of expertise. The next four chapters address the shaping of structure and the projection of meaning in performance, while the last four consider performance as analytical paradigm, as dramatic narrative, as act of criticism, as temporal process. Among the distinguished international authorship are many accomplished performers whose practical experience ensures that the book contains vital and stimulating insights into the interpretation of music, and that it will speak to a wide musical audience